Rational discovery of a highly novel and selective mTOR inhibitor. Issue 21 (1st November 2019) - Jin, Stanley; Mikami, Satoshi; Scorah, Nick; Chen, Young; Halkowycz, Petro; Shi, Lihong; Kahana, Jason; Vincent, Patrick; de Jong, Ron; Atienza, Joy; Fabrey, Robyn; Zhang, Lilly; et al.
Graphical abstract: Abstract: Aided by Structure Based Drug Discovery (SBDD), we rapidly designed a highly novel and selective series of mTOR inhibitors. This chemotype conveys exquisite kinase selectivity, excellent in vitro and in vivo potencies and ADME safety profiles. These compounds could serve as good tools to explore the potential of TORC inhibition in various human diseases.